The Influence of Environmental, Social, and Governance Performance on Foreign Investment - Amalia Siti Khodijah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study aims to investigate the effect of environmental, social, and governance (ESG) performance on foreign investment through corporate reputation.Design/Methodology/Approach: This study’s population was all non-financial companies listed on Indonesia Stock Exchange from 2015 to 2019. Moreover, the hypotheses testing technique used was Two-Stage Least Square (2SLS), with 150 observations distributed in balanced panel data. In addition, additional analysis was conducted to examine how each company paid attention to ESG practices based on its industry classification through descriptive statistical analysis.Research findings: The regression results revealed that companies with good ESG performance tended to have a high level of foreign investment. However, it could not be explained by the corporate reputation. In an additional test, this study documented that the mining industry had a much better ESG performance than other industrial groups.Theoretical contribution/Originality: This study pays attention to foreign investment through trading domestic equity shares, whereas previous studies only focused on ESG practices in the FDI process. In addition, this study examined corporate reputation in explaining the relationship.Practitioner/Policy implication: The research results can be used by standard setters in developing sustainability disclosure standards in Indonesia, which International Sustainability Standards Board is currently initiating.Research limitation/Implication: The weakness in this study is the small number of samples employed in the test due to the minimal availability of ESG data in the database.